Jihadi politics: the global jihadi civil war 2014-2019 - Hamming, Tore (Hurst & Company, 2022)
In February 2014, al-Qaida issued a statement that shocked the entire Jihadi movement. For the first time in its history, the group declared that a local affiliate, the Islamic State in Iraq, was no longer part of al-Qaida The renegade Iraqi group, led by Abu Bakr al-Baghdadi, had expanded its operations to Syria, taking over the regional branch Jabhat al-Nusra; but in the process, the group had defied orders from al-Qaida’s amir, Ayman al-Zawahiri. Islamic State’s actions, and increasingly aggressive posture towards fellow Jihadis, eventually ignited a Jihadi civil war–a period defined by internal tensions that ultimately turned global. With devastating impact, this fitna left the Jihadi movement more polarised and fragmented than ever, seriously threatening its internal cohesion. Jihadi Politics presents the first exhaustive account of infighting within the global Jihadi movement. Based on years of digital anthropology, hundreds of primary documents, and interviews with Jihadis, it offers an unprecedented glimpse into historic and current conflicts between and within Jihadi groups. This thorough examination of the years 2014-2019 offers a more nuanced understanding of the current state of Jihadism, with important insights into its future evolution–including Islamic State’s role in Afghanistan.